Energy use and economical analysis of seedy watermelon production for different irrigation systems in Iran. (November 2015) - Moradi, Rooholla; Rezvani Moghaddam, Parviz; Mansoori, Hamed
Abstract: Resource and energy use efficiency is one of the principal requirements of eco-efficient and sustainable agriculture. Seedy watermelon ( Citrullus vulgaris ; Joboni population) is irrigated by two methods including full and reduced irrigation systems in Iran. The objective of the present study was to compare seedy watermelon production in full (high input) and reduced (low input) irrigation systems in terms of irrigation water energy use efficiency (IWEUE), energy budget and economic analysis. Data were collected from 116 full irrigated and 93 reduced irrigated farms in northeast of Iran by using a face-to-face questionnaire in 2011–2012. The results showed that the total energy consumed under high input systems was 25625.94 MJ ha − 1, whereas under low input was 3129.3 MJ ha − 1 . IWEUE and all of the energy indexes were improved in the reduced irrigation system compared to the full condition. The direct and renewable energies in the reduced irrigation system were higher than full irrigation. The economical analysis indicated that higher return was gained by the full irrigation system due to higher yield compared to the reduced irrigation system. Human labor had the highest impact on seedy watermelon among the other inputs based on the Cobb–Douglas production function. Highlights: About 85% of used water irrigation in agriculture was supplied from groundwater in Iran. Reduced irrigation system improved the IWEUE and energy use efficiency. Direct and renewable energies were higher under reduced than full irrigation system. Reduced irrigation could be reduced irrigation water use up to 95% than full irrigation. Reduced irrigation system led to save the energy resource.